Bone‐Specific Metabolism of Dietary Polyphenols in Resorptive Bone Diseases. Issue 14 (25th June 2020) - Kunihiro, Andrew G.; Luis, Paula B.; Frye, Jennifer B.; Chew, Wade; Chow, H. H.; Schneider, Claus; Funk, Janet L.
Abstract : Scope: Curcumin prevents bone loss in resorptive bone diseases and inhibits osteoclast formation, a key process driving bone loss. Curcumin circulates as an inactive glucuronide that can be deconjugated in situ by bone's high β‐glucuronidase (GUSB) content, forming the active aglycone. Because curcumin is a common remedy for musculoskeletal disease, effects of microenvironmental changes consequent to skeletal development or disease on bone curcumin metabolism are explored. Methods and results: Across sexual/skeletal development or between sexes in C57BL/6 mice ingesting curcumin (500 mg kg −1 ), bone curcumin metabolism and GUSB enzyme activity are unchanged, except for >twofold higher ( p < 0.05) bone curcumin‐glucuronide substrate levels in immature (4–6‐week‐old) mice. In ovariectomized (OVX) or bone metastasis‐bearing female mice, bone substrate levels are also >twofold higher. Aglycone curcumin levels tend to increase proportional to substrate such that the majority of glucuronide distributing to bone is deconjugated, including OVX mice where GUSB decreases by 24% ( p < 0.01). GUSB also catalyzes deconjugation of resveratrol and quercetin glucuronides by bone, and a requirement for the aglycones for anti‐osteoclastogenic bioactivity, analogous to curcumin, is confirmed. Conclusion: Dietary polyphenols circulating as glucuronides may require in situ deconjugation for bone‐protective effects, a process influenced by bone microenvironmental changes. Abstract : Curcumin and other dietary polyphenols are bone‐protective and block RANKL‐stimulated osteoclastogenesis. Inactive glucuronide metabolites circulating in vivo are deconjugated locally in bone by β‐glucuronidase (GUSB) to form the bioactive aglycones. Bone GUSB and aglycone levels remain fairly constant across skeletal development and resorptive diseases, including high turnover states, like osteoporosis, where bone glucuronide substrate levels are increased.